DAYA TARIK WISATA PADA DESTINASI WISATA ZIARAH MAKAM SYEKH ABDURRAHMAN SIDDIQ DI HIDAYAT KABUPATEN INDRAGIRI HILIR - Fatimah, Siti; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to identify and understand the various tourist attractions found at the religious tourism destination of Makam Syekh Abdurrahman Siddiq, located in Hidayat, Indragiri Hilir Regency, Riau. The research uses a descriptive qualitative approach with data collected through interviews, observations, and documentation. The findings indicate that the main attraction of this destination lies in the religious and historical values attached to Syekh Abdurrahman Siddiq as a prominent Islamic scholar and Mufti of the Indragiri Kingdom. Pilgrimage activities, the "maantar niat" tradition, and regular religious rituals such as prayer gatherings, habsyi (Islamic musical recitation), suluk (spiritual retreat), and the annual Haul event are key elements that attract visitors. Tourists come not only from local areas but also from outside the region, such as Bangka, demonstrating the tomb’s widespread spiritual influence. In addition, physical factors such as the renovated tomb building, peaceful religious atmosphere, and supporting facilities like rest areas and local vendors contribute to a more complete visitor experience. These findings support theories that strong tourism attractions significantly impact visitor interest, particularly in the context of religious tourism. Keywords: tourist attraction, religious tourism, makam syekh abdurrahman siddiq, visitor interest